Estudio comparativo entre la técnica oscilométrica y el método de Riva-Rocci para la medición no-invasiva de la presión arterial en el medio ambiente hospitalario - Azpiroz Leehan, Joaquín; Godínez, Rafael (Revista Mexicana de Ingenieria Biomedica, 2002)
We present a comparative study between the conventional Riva-Rocci technique for the non-invasive measurement of blood pressure, and the digital oscillometric device. The objective is to evaluate the oscillometric device in a clinical setting. We present the methodology employed, the results and the statistical analysis, and we conclude that, for this specific device, the repeatability and reliability are not up to the standards in a hospital environment